Molecular analysis of long COVID and new-onset diabetes mellitus: pathobiological relationships and current mechanistic views - Shitaye, Getasew; Getie, Muluabay; Mekonnen, Zewdie; D’Abrosca, Gianluca; Fattorusso, Roberto; Isernia, Carla; Amuamuta, Asmare; Malgieri, Gaetano (Frontiers in Endocrinology, 2025)
Long COVID, or post-acute sequelae of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (PASC), refers to a range of persistent health effects associated with SARS-CoV-2 infection. Long COVID is a complex, multisystem disorder that can affect nearly every organ system and is strongly linked with the incidence of diabetes and other chronic conditions. Increasing evidence also connects persistent SARS-CoV-2 infection with the development of new-onset diabetes and other metabolic disorders. In this review, we assess the current evidence and discuss the incidence of new-onset diabetes, along with the pathobiological mechanisms by which SARS-CoV-2 may contribute to the progression of both new-onset type 1 and type 2 diabetes mellitus (T1DM and T2DM). We summarize the latest understanding of the molecular and cellular mechanisms underlying SARS-CoV-2–associated new-onset diabetes. Potential mechanisms include direct damage to pancreatic β-cells, inflammation, insulin resistance, and autoimmune responses. Dysregulation of the ACE2/renin–angiotensin system (RAS) pathway has been linked to multiple inter-organ pathologies, and increased inflammatory cytokines together with dysregulation of interferon regulatory factors (IRFs)—such as overexpression of IRF1—appear to represent key mechanistic links to widespread tissue damage and metabolic alterations. Moreover, the presence of viral RNA or viral RNA fragments may directly damage pancreatic islets, contributing to insulin resistance and β-cell dysfunction that, in turn, may promote the development of new-onset diabetes. In light of these findings, this review further examines evidence supporting the persistence of SARS-CoV-2 RNA in PASC reservoir tissues, including the pancreas, and its potential association with the development of new-onset diabetes mellitus.